Faktor-Faktor Pertumbuhan Laba pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia - Nasution, Abdillah Arif; Nasution, Aulia Arif; Br Sitepu, Yuni Lestari; Putra, Adi Syah; Parluhutan, Taufik Akbar (Politeknik Ganesha Medan, 2024)
The purpose of this study is to identify the variables that affect profit growth. Secondary data is the sort of data employed in this associative research method. Purposive sampling was utilized to choose the sample from the population of 67 manufacturing businesses that were listed on the Indonesia Stock Exchange for the years 2017 through 2021. Multiple linear regression on panel data and descriptive statistical analysis are the methods utilized for data analysis. The research's findings indicate that the current ratio and inventory turnover have a negative and insignificant impact on profit growth, while the total asset turnover has positive and significant effects on profit growth, and debt to equity ratio has negative and significant effects on profit growth. As both excellent and bad profit growth will directly affect a company's financial condition, it is envisaged that determining profit growth will be a key concern for any business. The consequences of inaccurately estimating profit growth will be extensive. Given that these factors have been shown to have an impact on the company's profit growth, management should pay close attention to the factors that affect profit growth, particularly determining total asset turnover,and debt to equity ratio, so that the company can determine the best possible profit growth.